The Effect of Sodium Humate on Sheep In Vitro Fermentation Characteristics and Rumen Bacterial Community - Na Yin; Yuchao Hu; Xiangting Cai; Long Gao; Wenwen Wang; Yuan Wang; Jingwei Qi (Microorganisms)
This study aimed to determine the optimal supplementation level of sodium humate (SH) for improving rumen fermentation efficiency in vitro. Using rumen fluid from four donor ewes with three experimental replicates per treatment, we evaluated a basal diet supplemented with SH at 0 (control), 0.5 (SH0.5), 1 (SH1), and 2 (SH2) g/kg dry matter. The results of this study revealed that after 12 h of incubation, compared to the control group, the SH0.5 group significantly decreased gas production (GP) by −11.66% (p < 0.01). There were no significant differences in pH values, bacterial crude protein (BCP) content, and ammonia nitrogen (NH₃-N) concentration among the groups (p > 0.05). After 24 h of incubation, no significant differences in pH values were observed among the groups (p > 0.05). The SH1 group exhibited significantly higher BCP content compared to other treatments (p < 0.05), concomitant with a marked reduction in NH₃-N concentration (p < 0.01). Compared to the control group, GP in the SH1 group increased significantly by 7.16%, and a significant increase of 5.43% (p < 0.05), while it decreased significantly by −9.96% in the SH0.5 group (p < 0.01). However, no significant differences in volatile fatty acids were observed among the groups after either 12 or 24 h of fermentation. The addition of 1 g/kg SH altered the composition of the rumen bacterial community, which was indicated by the increased relative abundances of Prevotella, Anaerovibrio, and Saccharofermentans and the decreased relative abundances of Actinobacteriota, Lachnospiraceae_NK3A20_group, and [Ruminococcus]_gauvreauii_group (p < 0.05). Furthermore, Anaerovibrio was negatively correlated with NH₃-N and positively correlated with gas production, while [Ruminococcus]_gauvreauii_group was negatively correlated with gas production. The study indicates that the addition of 1 g/kg SH optimizes rumen fermentation efficiency and improves nutrient utilization by modulating the structure and composition of the bacterial community, thus serving as an effective additive for enhancing rumen fermentation and feed utilization in ruminants.